Analisis Efektivitas Penggunaan E-Wallet dalam Pembayaran Digital Bagi Mahasiswa Program Studi Manajemen Bisnis Syariah UMSU - Ferry Rian Maulana; Isra Hayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to assess the effectiveness of using e-wallets in digital transactions among students of the UMSU Sharia Business Management Study Program. With a qualitative approach, this field research describes phenomena related to e-wallets. The research results show that e-wallets are effective in facilitating student transactions, especially in terms of convenience, speed and security, even though there are challenges such as limited technological knowledge and technical problems. E-wallets are increasingly popular and are widely used for online transportation payments, e-commerce, and delivery services. Security, through a verification system, is also a major attraction for students.